TRANSFORMASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS TEKNOLOGI DIGITAL DI ERA SOCIETY 5.0 - Muhammad Ilham Jaya Kesuma; Ilham Fatoni; Ikhtiar Cahya Ajir; M. Izzad Khairi Yazdi; Agus Pahrudin; Ali Murtadho; Achi Rinaldi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of technology in the Society 5.0 era requires the world of education, including Islamic Religious Education, to transform in order to present a relevant, adaptive, and future-oriented learning model. This transformation does not only change the teaching media, but also includes a shift in the learning paradigm, methods, and strategies that combine Islamic values ​​with advances in digital technology. This study aims to examine the implementation of the transformation of Islamic Religious Education learning based on digital technology in the Society 5.0 era. This study uses a qualitative approach with a literature study research method carried out through a critical review of various literatures that discuss the digitalization of Islamic education and its implementation in the context of Islamic Religious Education learning. The results of the study identified three main aspects in the transformation of Islamic Religious Education learning based on digital technology in the Society 5.0 era. First, the integration of digital technology through the use of online platforms, learning applications, and interactive media that support flexible and contextual learning. Second, the shift in approach from teacher-centered to student-centered learning, where students become active subjects in the learning process based on digital experiences. Third, challenges that include the gap in access to digital infrastructure, limited teacher competence in digital pedagogy, and the need to strengthen digital literacy and ethics based on Islamic values. This study concludes that the success of PAI transformation based on digital technology requires synergy between teachers, educational institutions, and policy makers through increasing human resource capacity, providing infrastructure, and curriculum innovation that supports the integration of technology and Islamic values. This study recommends further field-based research to explore the implementation of digital PAI learning in various educational units.